Preparation of palm oil methyl esters for alkenyl succinic anhydride production - Nur Azreena Idris,; Loh, Soh Kheang; Choo, Yuen May; Boey, Peng Lim (Universiti Kebangsaan Malaysia, 2010)
The fractions of fatty acid methyl esters (FAME) i.e. crude palm oil methyl esters (CPOME), RBD palm olein methyl esters (RBD Palm Olein ME) and used frying oil methyl esters (UFOME) rich in unsaturated fatty esters were used to prepare alkenyl succinic anhydrides (ASA). The fractions were obtained via fractional distillation that separated the unsaturated fatty esters from the saturated fatty esters. The fractions with the highest content of unsaturated fatty esters were reacted with maleic anhydride (MA) for 8 hours at 240oC with the MA/FAME ratio of 1.5. The reaction was conducted without catalyst and solvent. The crude alkenyl succinic anhydride (ASA) obtained was purified by column chromatography. The purified compound was characterised by FTIR.